The socio-cultural factors behind the Saudi attitude toward COVID-19 vaccination: A survey-based study - Al-Ghuraibi, Muna; Dighriri, Ibrahim M.; Elrggal, Mahmoud Essam; Obaid, Najla A. (Frontiers in Public Health, 2023)
Vaccine distrust and rejection are thought to contribute to disease outbreaks and greater mortality. The current study aims to analyze Saudi population socio-cultural characteristics and attitudes toward the vaccine intake. The study was cross-sectional survey-based approach. An online questionnaire was used in by performing a snowball method. A total of 444 people responded, of whom 333 (75%) were female, and 111 (25%) were males. The demographic characteristics associated with vaccine confidence were gender, job type, medical problems, and knowledge about COVID-19 symptoms. The hesitancy was highest percentage (31.17%) among individuals aged 21–30 years old and in male more (27.03%) than female (25.23 %). However, if we focused on the percentage of the refusal to get the vaccine, female have the highest percentage of refusal (15.23 %) than male (4.5%). More than third of the vaccine hesitant responded had limited knowledge about COVID-19 symptoms. However, personal characteristics associated with vaccine confidence were described as the following; do not fully agree to trust in vaccines produced in a short time (42.1%), fear of the future results of the vaccines (30.4%), reluctance to allow a foreign material to enter the body (17.6%), no interaction with others, so no need of the vaccine (11.5%); low interaction with people (67.8%) and reluctance to make decisions (11.3%). The most social motivation to get the vaccine was to get back to normal life (67.6%). Our study reveals that more than half of the respondents in Saudi Arabia were confident about the vaccine (61.7%), compared with 25.7% who were hesitant and 12.6% who were unconvinced. Based on that these results in the early period of the COVID-19 vaccine introduction to the country (early 2021) and before any governmental allowance and political intervention, we found that the socio-demographic and the social/ cultural characteristics of the population are significant factors contribute to vaccination acceptance. Thus, policymakers should support long-term vaccination safety studies, conduct educational programs with high-priority populations' health and vaccination hesitancy reduction techniques may be tailored to local communities.